Thermoluminescence Characterization of Irradiation Property of SiC Material - LIU Haisheng, LIU Malin (Yuanzineng kexue jishu)
High temperature gas cooled reactor is an advanced type of reactor with fourth generation characteristics, and the core uses fuel elements composed of TRISO fuel particles. Among them, 35 μm thick 3c-SiC coating layer is a key layer for resistance of internal pressure, preventing the release of fission products, and efficiently conducting core heat energy, and is one of the key barriers to ensure safety. The purpose of this study is to evaluate the defects of 3c-SiC materials and the changes in 3c-SiC defects after irradiation using thermoluminescence (TL) method. Based on the theoretical analysis of intrinsic defects and impurity related defects in the preparation process of SiC materials, the luminescence properties of 3c-SiC materials were experimentally studied using gamma ray irradiation and TL analysis. The TL luminescence intensity of SiC crystal materials increases with increasing irradiation dose. The luminescence peak after irradiation can be described by the TL second-order kinetic equation. Its intrinsic defect concentration can be characterized by the 390 ℃ luminescence peak of TL. In the irradiation environment, downloading energy particles causes Si and C atoms to deviate from the crystal lattice position, resulting in point defects such as supersaturated vacancies, interstitial ions, and misaligned atoms, which are manifested as an additional luminescence peak of 194.5 ℃ approximately. TL is a good method for characterizing defects and analyzing radiation performance of SiC materials. 1 600 ℃ is the ideal deposition temperature for SiC materials. It has good reference value for studying the defects and performance analysis of SiC coating layers, and has certain reference significance for characterizing the performance of SiC coating layers before and after irradiation.